Caffe2 Quick Start Guide: Modular and Scalable Deep Learning Made Easy - Nanjappa, Ashwin (Packt Publishing, Limited, 2019)
Caffe2 by Facebook is a popular and relatively lightweight deep learning framework. Caffe2 is known for speed, accuracy and high efficiency in training neural networks. Caffe2 is widely used in mobile apps. This book is a fast paced guide that will teach you how to train and deploy deep learning models with Caffe2 on resource constrained platforms.